Importancia de la innovación en el sector agropecuario: caso uso de drones no tripulados en la provincia de El Oro. - Alvarado Menendez, Kleber Andres (Machala : Universidad Técnica de Machala, 2022)
There have been several agricultural revolutions throughout history. Among these, the last one, known as agriculture 4.0, includes the implementation of innovation, scientific research, social sustainability and technology transfer within agriculture. Ecuador is a country with the resources to become an agri-food power. However, the lack of integration of knowledge management in agricultural activities has triggered a comparable delay with developed countries. The province of El Oro has a significant participation with the production of export bananas, establishing itself as the third largest in Ecuador. Despite this, during 2021, the banana sector had a decrease in investments compared to the previous year. Factors such as high prices for disease control, agricultural inputs, fuel, lack of labour, and technical assistance significantly affected productivity. Therefore, there is an opportunity for agro-industrial development that includes the use of precision agriculture within the banana production sector. It is relevant to know that the union between technology and the Orense agricultural sector with the implementation of drones, would allow a productive development that would generate an increase in productivity for the agribusiness sector with benefits that include precision agriculture, care for the environment, and quantitative analysis at all stages of crop development.
Han existido varias revoluciones agrícolas durante la historia. Entre estas la última, conocida como agricultura 4.0, incluye la implementación de innovación, investigación científica, sostenibilidad social y transferencia tecnológica dentro de la agricultura. Ecuador es un país con recursos para llegar a ser una potencia agro alimentaria. Sin embargo, la falta de integración de la gerencia del conocimiento en las actividades agropecuarias ha desencadenado un retraso comparable con los países desarrollados. La provincia de El Oro tiene una participación significativa con la producción de banano de exportación, estableciéndose como la tercera más grande del Ecuador. A pesar de ello, durante el 2021, el sector bananero tuvo un decrecimiento en las inversiones con respecto al año anterior. Factores como los altos precios para el control de enfermedades, insumos agrícolas, combustibles, falta de mano de obra y asistencia técnica afectaron notablemente la productividad. Por ello, existe la oportunidad de desarrollo agro industrial que incluye la utilización de agricultura de precisión dentro del sector productivo el bananero. Es relevante conocer que la unión entre la tecnología y el sector agropecuario orense con la implementación de drones, permitiría un desarrollo productivo que generaría aumento de productividad para el sector agro empresarial con beneficios que incluyen una agricultura de precisión, cuidado al medio ambiente, y análisis cuantitativos del cultivo en todas las etapas de desarrollo.
Keywords: INNOVACIÓN; SECTOR AGROPECUARIO; DRONES; AGRICULTURA 4.0